THE EXISTENCE OF THE ELECTION SUPERVISORY AGENCY POST 2024 BASED ON POSITIVE LAW - Murjani Murjani; Suwardi Sagama (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2022)
Bawaslu was formed to oversee elections and elections to run in a direct, free, confidential, honest, and fair manner. Bawaslu's authority is only to supervise in stages. In 2024, elections and elections will be held simultaneously. The stages will start again before the elections and elections in 2029. Researchers are interested in knowing the existence of Bawaslu post-election and elections in 2024. The research uses a normative legal research method with a statutory approach. Based on Law Number 7 of 2017 concerning Elections, Bawaslu only has supervisory authority at the election and election stages for 20 months. Bawaslu oversees the stages set by the KPU based on the PKPU. After the general election and simultaneous elections in 2024, Bawaslu does not have supervisory authority until it enters the stages for implementation in 2029. The existence of Bawaslu without any supervisory activities can return to being an ad hoc body at the beginning of its formation.